2003
DOI: 10.1007/s00122-003-1212-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex-linked AFLP markers indicate a pseudoautosomal region in hemp (Cannabis sativa L.)

Abstract: In dioecious plants of hemp ( Cannabis sativa L.), males are regarded as heterogametic XY and females as homogametic XX, although it is difficult to discriminate the X cytologically from the Y. The Y chromosome is somewhat larger than the X. Our aim was to analyse AFLP markers on X and Y, and to use them to gain some insight into the structure of the sex chromosomes. Markers located on the sex chromosomes can be grouped into different classes, depending on the presence or absence of a fragment on the X and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Therefore, the usefulness of these markers in MAS is still uncertain. In a later work, Peil et al (2003) assigned 43 more AFLP markers to the Y chromosome, on the basis of the complete linkage of these markers with the male sex in a progeny of 80 plants deriving from a male × female cross; besides, the observation of the skewed segregation ratios of several other markers led the authors to hypothesize the existence, on the Y chromosome of male plants, of a region (pseudoautosomal region, PAR), able to recombine to some extent with the corresponding portion of the X chromosome, similarly to what observed in other dioecious species with sex chromosomes (Di Stilio et al, 1998). Other research groups described markers linked to the male sex (NCBI nucleotide sequences AF364954 and AF364955,MADC5 and MADC6,by Torjek et al), and also female-associated RAPD markers were reported (Shao et al, 2003), though in the latter case no chromosome-specific location can be hypothesized, and it was not specified whether this marker was able to distinguish female from monoecious plants.…”
Section: Dna Markers and Sex Phenotypementioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, the usefulness of these markers in MAS is still uncertain. In a later work, Peil et al (2003) assigned 43 more AFLP markers to the Y chromosome, on the basis of the complete linkage of these markers with the male sex in a progeny of 80 plants deriving from a male × female cross; besides, the observation of the skewed segregation ratios of several other markers led the authors to hypothesize the existence, on the Y chromosome of male plants, of a region (pseudoautosomal region, PAR), able to recombine to some extent with the corresponding portion of the X chromosome, similarly to what observed in other dioecious species with sex chromosomes (Di Stilio et al, 1998). Other research groups described markers linked to the male sex (NCBI nucleotide sequences AF364954 and AF364955,MADC5 and MADC6,by Torjek et al), and also female-associated RAPD markers were reported (Shao et al, 2003), though in the latter case no chromosome-specific location can be hypothesized, and it was not specified whether this marker was able to distinguish female from monoecious plants.…”
Section: Dna Markers and Sex Phenotypementioning
confidence: 85%
“…Male-associated markers have been described also using AFLPs Peil et al, 2003). In this case, however, there have apparently been problems in the correct scoring of the sexual phenotype, especially in the case of field-grown plants.…”
Section: Dna Markers and Sex Phenotypementioning
confidence: 99%
“…RAPDs, RFLPs, AFLPs and microsatellite Y-linked markers have been previously detected in diVerent dioecious plants (Jiang and Sink 1997;Mulcahy et al 1992;Di Stilio et al 1998;Zhang et al 1998;Sakamoto et al 1995); but the use of a BSA approach in male and female oVspring from a controlled cross has allowed us to identify RAPD markers that were linked not only to the Y but also to the X chromosomes of this R. acetosa. Given the dominant nature of these markers, the BSA approach does not allow the recognition of X-linked markers that are heterozygous in the female parents (Peil et al 2003), and therefore the number of the identiWed X-linked markers was low.…”
Section: Discussionmentioning
confidence: 99%
“…AFLP was also utilized for male associated DNA sequence generation (Flachowsky et al 2001;Peil et al 2003). Datwyler and Weiblen (2006) reported that it was possible to discriminate illegal, potent marijuana cultivars from hemp plants via PCoA of AFLP variation.…”
Section: Discussionmentioning
confidence: 99%